Implementasi Game Design Document Pada Perancangan Game Based Learning - Dani Arifudin; Suliswaningsih Suliswaningsih; Dian Pramesti; Linda Heryanti (CogITo Smart Journal, 2022)
Several studies regarding the selection of game-themed learning models concluded that they can eliminate boredom in the learning process, so that students are enthusiastic and play an active role in following the lessons, this game-themed learning is called Game Based Learning. That is a learning method that has the concept of combining educational content or learning principles with games that aim to attract students to learn. In designing game-based learning, of course, it must be well structured and conceptualized, and meet the standards for applying game concepts to learning. A method that can record and document every detail of gameplay design and game based learning design is the Game Design Document (GDD). This study aims to implement GDD in game based learning design, using the Multimedia Development Life Cycle (MDLC) method. It is hoped that this research can produce conclusions regarding game-based learning design standards documented in GDD.